Masyarakat Terasing: Alienasi Masyarakat Lokal pada Pembangunan Ibu Kota Nusantara (IKN) - Hasanah, Nur; Hamid, Ismar (Huma: Jurnal Sosiologi, 2025)
The development of Indonesia’s new capital city (IKN) in East Kalimantan is often promoted as a symbol of progress and equality; however, in reality, it generates significant marginalization. This project not only neglects the voices of local communities but also shifts their role from being subjects of development to mere objects of it. This research aims to critically explore the forms of social alienation experienced by local communities as a result of exploitative development policies. Using a qualitative approach with a phenomenological method, data were collected through participatory observation, in-depth interviews, and field documentation. The findings reveal that the Paser Balik community experiences four dimensions of alienation as described by Karl Marx: alienation from the product of labor (loss of control over land and resources), alienation from the labor process (displacement of traditional economic practices), alienation from the self (disconnection from identity and spiritual ties to ancestral land), and alienation from the social environment. The analysis demonstrates that IKN development is non-inclusive, marginalizing communities from their land, work, identity, and social environment. This study offers a novel critical understanding of how IKN development generates processes of alienation for local communities, and its implications for their identity, roles, and empowerment within the context of social change and modernization. Further research could explore more deeply the role of the state and development institutions in either reinforcing or weakening the position of local communities in strategic projects, as well as examine alternative development models grounded in participation and social justice.